DAYA SAING USAHA BUDIDAYA RUMPUT LAUT (Eucheuma Spinosum) - Hasna, Hasna; Mardiyati, Sri; Razak, A Rosdianti; Rahmawati, Rahmawati (Universitas Muhammadiyah Makassar, 2021)
Seaweed is one of the commodities that are widely cultivated in coastal areas in Indonesia, as an export-oriented commodity. This study aims to determine the competitive advantage, comparative advantage, and competitiveness of seaweed farming (Eucheuma Spinosum). This research was conducted in Liya Bahari Village, Wangi-Wangi Selatan District, Wakatobi Regency. The method of determining the sample is purposive sampling. This research was conducted from July to August 2021. The data sources are primary and secondary data. Analysis of the data used is PAM (Policy Analysis Matrix). The results of this study indicate that seaweed farming in Liya Bahari Village, Wangi-Wangi Selatan District, Wakatobi Regency has a competitive advantage and comparative advantage, and has strong competitiveness. The seaweed farming has a Domestic Resource Cost Ratio (DRC) of 0.03. The value of DRC < 1 indicates that seaweed farming has a comparative advantage so that it has domestic resource efficiency at international prices. The seaweed farming has a Private Cost Ratio (PCR) value of 0.40. The value of PCR < 1 indicates that seaweed farming has a competitive advantage and has domestic resource efficiency at the actual price.